Automatic Distribution of PRVs for Leakage Reduction - Ramon Pérez; Guillem Roca; Sergi Grau (Engineering Proceedings)
In this work, an automatic distribution of the pressure reduction valves (PRVs) is proposed. First, a well-calibrated hydraulic model is required. The model of Manresa, a city of Catalunya in the Mediterranean area, was calibrated using pressure sensors, and the background leakage was estimated using weighted emitter coefficients. Simulating the model in real boundary conditions highlights the areas of maximum background leakage. The manual introduction of a PRV shows its effectiveness regarding leakage reduction. An algorithm for finding the high-pressure areas and their boundary pipes is presented. The introduction of the PRV, taking into account the flow constraints, produces a new scenario. Finally, the leakage reduction thanks to the pressure control by means of new actuators is evaluated. The leakage is reduced by around 6%.